Chloroquine modulates antitumor immune response by resetting tumor-associated macrophages toward M1 phenotype - Degao Chen (Nature Portfolio, 2018)
Tumour-associated macrophages (TAMs) display an M2 phenotype that promote tumour immune escape. Here the authors show that Chloroquine (CQ), a lysosome inhibitor used against malaria, inhibits tumour growth by switching TAMs into an M1 tumor-killing phenotype by repolarizing macrophages metabolism.